Diseño de un sistema de información para la gestión del mantenimiento de los equipos biomédicos de la clínica veterinaria para pequeños animales en la universidad Antonio Nariño sede Popayán. - Figueroa Revelo, Daniel Alejandro (Universidad Antonio Nariño, 2023)
The management of biomedical technology in veterinary clinics plays an important role in the control of the different types of maintenance of biomedical equipment; therefore, the need arises to offer a system that addresses all the information necessary for the maintenance of biomedical technology in the veterinary clinic. It is important to recognize that management systems allow the organization to have a better control of the processes that are executed during the operation, to the extent that time is optimized and a better use can be made of resources, In the particular case of biomedical equipment, it allows planning maintenance, among other things, in order to guarantee the availability of the equipment, which is important because biomedical equipment is necessary during care because it favors animal welfare, as it is part of the diagnostic and treatment tools, and also reduces the use of paper, which provides the opportunity to reduce expenses. The management system was developed by means of code management through java language, with three roles which are the administrator, the director of the clinic and a free role for students and other officials, which effectively generated the delivery in the veterinary clinic, where it was left installed and working as expected.